Sharp weighted bounds for the q‐variation of singular integrals. (11th January 2013) - Hytönen, Tuomas P.; Lacey, Michael T.; Pérez, Carlos
Abstract : We extend the sharp weighted bound of the A 2 theorem to the q ‐variation norm of certain Calderón–Zygmund operators ( q >2), a stronger nonlinearity than the maximal truncations that have been treated before. We obtain this result by a new non‐probabilistic approach that was independently discovered by Lerner.